Efficacy of 2-phenoxyethanol as an anaesthetic for two size classes of white sea bream, Diplodus sargus L., and sharp snout sea bream, Diplodus puntazzo C - Tsantilas, H.; Galatos, A. D.; Athanassopoulou, F.; Prassinos, N. N.; Kousoulaki, K. (Aquaculture, 2006)
The objective of this study was to evaluate the efficacy of 2-phenoxyethanol as an anaesthetic for two size classes of white sea bream, Diplodus sargus L. (30 and 60 g), and sharp snout sea bream, Diplodus puntazzo C., (15 and 30 g) and establish the minimum concentration producing desirable anaesthetic effects on them. Fish were exposed to concentrations varying from 0.1 to 0.4 mL/L for a 60-min period. At concentrations of 0.1, 0.117 and 0.133 mL/L, 2-phenoxyethanol failed to induce anaesthesia, whereas at concentrations of 0.167, 0.2, 0.3 and 0.4 mL/L all the fish were anaesthetised within 3 min of exposure. However, mortality was observed with the two higher concentrations. Induction time decreased and recovery time increased with increasing concentrations, being significantly concentration-dependent in both species (P ≤ 0.01). Following exposure of D. sargus to concentrations of 0.2 or 0.3 mL/L, both induction and recovery time were significantly weight-dependent (P ≤ 0.01). However, erratic weight dependencies of both induction and recovery time were observed in D. puntazzo. 2-Phenoxyethanol proved to be an effective and safe anaesthetic in both species permitting rapid and uneventful induction and recovery after a 60-min exposure period. The minimum concentration producing desirable anaesthetic effects was 0.167 mL/L. © 2005 Elsevier B.V. All rights reserved.